2010
DOI: 10.1016/j.ceca.2009.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying calcium fluxes underlying calcium puffs in Xenopus laevis oocytes

Abstract: SummaryWe determine the calcium fluxes through inositol 1,4,5-trisphosphate receptor/channels underlying calcium puffs of Xenopus laevis oocytes using a simplified version of the algorithm of Ventura et al., 2005 [1]. An analysis of 130 puffs obtained with Fluo-4 indicates that Ca 2+ release comes from a region of width ~ 450 nm, that the release duration is peaked around 18ms and that the underlying Ca 2+ currents range between 0.12 and 0.95pA. All these parameters are independent of IP 3 concentration. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 34 publications
11
66
0
Order By: Relevance
“…I , Z = 2 and F represent the Ca 2+ current passing through the channel, valence of Ca 2+ and Faraday's constant respectively. Previous studies have concluded that a single InsP 3 R channel releases a current of about 0.05-0.5 pA [8,19,20]. Throughout this manuscript we will assume a standard single-channel current of I = 0.05 pA when the channel is open, and zero otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I , Z = 2 and F represent the Ca 2+ current passing through the channel, valence of Ca 2+ and Faraday's constant respectively. Previous studies have concluded that a single InsP 3 R channel releases a current of about 0.05-0.5 pA [8,19,20]. Throughout this manuscript we will assume a standard single-channel current of I = 0.05 pA when the channel is open, and zero otherwise.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental observations suggest a simultaneous opening of 6-10 channels during a Ca 2+ puff (a Ca 2+ release event caused by a simultaneous opening of more than one channel in a cluster) [5,6] and a typical cluster diameter of about 0.5 μm [5,7,8]. We assume that the maximum number of simultaneously open channels ever observed at a given puff site represents the number of channels within the cluster giving a mean inter-channel spacing of about 100-150 nm depending on the size and number of channels within a cluster.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous analyses (Bruno et al 2010), the model assumes that a cluster occupies a circle of fixed radius, R = 250 nm, and that N IP 3 Rs are randomly distributed inside it with uniform probability. The model has been developed for data collected from similar-type clusters, so that the value of N is also fixed.…”
Section: The Modelmentioning
confidence: 99%
“…The aim is to determine how r inf should be varied in the model to account for the presence of these added buffers. To this end, we simulate the reaction-diffusion system that models the dynamics of cytosolic Ca 2+ as described in Solovey et al (2008) in the presence of one open IP 3 R. An open IP 3 R is considered to be a point source that releases a constant Ca 2+ current that was estimated from experimental data to be 0.1 pA (Bruno et al 2010). The reaction-diffusion system (Solovey et al 2008) also includes a cytosolic Ca 2+ indicator dye and an exogenous buffer, either ethylene glycol tetraacetic acid (EGTA) or bis(2-aminophenoxy)ethane tetraacetic acid (BAPTA).…”
Section: Intracluster Ca 2+ Distribution In the Presence Of Differentmentioning
confidence: 99%
See 1 more Smart Citation